ANALISIS PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, DAN STRATEGI MANAJEMEN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Lulu Inayah (2021)
This research is a quantitative study which aims to determine the effect of company size, financial distress, and management strategy on going concern audit opinion. This study uses manufacturing companies listed on the Indonesia Stock Exchange as a population. The selection of data samples was determined using the cluster sampling method and obtained 36 manufacturing companies were collected as the research sample. Hypothesis testing in this study used logistic regression analysis with the SPSS version 25 program and a significant level of 5%. The results of this study indicate that company size has not significant effect on going concern audit opinion, financial distress significant effect on going concern audit opinion and management strategy has not significant effect on going concern audit opinion.